El Sínodo de los Obispos (2015): la "propositio" sobre los fieles divorciados y casados de nuevo civilmente - Aznar Gil, Federico R. (Revista española de derecho canónico, 2015)
The author, following on from his previous writings on the ecclesial situation of those faithful who divorce and then remarry civilly in the III Extraordinary General Assembly of the Synod of Bishops of 2014, analyses this question in the final propositions of the Synod of the Bishops of 2014; in the Instrumentum laboris of 2015; and finally in the XIV Ordinary Assembly of the Synod of the Bishops 2015, analysing the ecclesial attention towards those faithful which, in an attempt to bring together the different feelings which surfaced at the Synod, has been formulated ambiguously, meaning that this will give rise to the differering interpretations and praxis